CRIAÇÃO DO BANCO DE DADOS "FARMACEOMA / PHARMACEOME” - Nonnenmacher, Carine L.; Silva, Luiz A. A. d.; Goudochnikov, Viktor I.; Rohden, Rafael B.; Konzen, Michel; Dill, Sérgio L. (Salão do Conhecimento, 2013)
Resumo